An artistic research proposal from an A/R/TOGRAPHY perspective: a study of Strauss’s oboe concerto - López-Peláez-Casellas, Maria Paz; García-Herrera, Cecilio (Música Hodie, 2019)
This article is a contribution to the debate which has been taking place for some years now around the use of artistic research methodologies in conservatories. To be precise, it supports a methodology centred on artistic activity, which is not conditioned by the dictates of science and the need to obtain results. Within this current of thought, we have developed a new methodology of artistic research, a/r/tography, which is adapted from Fine Arts, and is aimed at teachers in music conservatories and makes it possible to simultaneously research, perform and teach a piece of music.